Exchange Rate Fluctuation on Emerging Market and Developing Countries in Europe - Nabilah Khairunnisa; Idah Zuhroh (Center for Economics, Business and Entrepreneurship Development Faculty of Economics and Business, Universitas Muhammadiyah Malang, 2022)
This study investigates the determinants of the exchange rate in European Emerging Market and Developing Countries (EMDEs), including Albania, Bulgaria, Hungary, Rep. Moldova, Rep. North Macedonia, Romania, Russia, and Ukraine. This study uses secondary data from 2000-2019 in time series and panel data with a sample of 8 countries sourced from the United Nations Conference on Trade and Development, the International Monetary Fund, and the World Bank. A regression method was used for time series data to analyze each country, and panel data was used for eight countries. Time series regression results show the influence of different relationships in each country. Meanwhile, the panel data regression found that exchange rate fluctuations in EMDE's European countries, GDP growth, and Terms of Trade (ToT) had a significant positive effect on exchange rates. It means that an increase in GDP and ToT growth affects the exchange rate appreciation, and a decrease in GDP and ToT growth affects the exchange rate depreciation in EMDE's European countries. Meanwhile, inflation and loan interest rates have a significant adverse effect on the exchange rate. It means that every decrease in inflation and interest rates on loans affects the appreciation of the exchange rate and vice versa, increases in inflation and interest rates on loans result in exchange rate depreciation in EMDE's European countries.